EFFECTIVENESS OF FAMILY-CENTERED EMPOWERMENT MODEL IN COMPLEMENTARY FEEDING TO PREVENT STUNTING IN COMMUNITIES, INDONESIA - Muflih Muflih; Tri Khasana; Dheska Arthyka Palifiana; Rahayu Widaryanti (Indonesian Journal of Community Health Nursing, 2026)
Introduction: Stunting remains a critical public helath issue in Indonesia. This study aimed to develop and evaluated the effectiveness of a Family-Centered Empowerment Model (FCEM) intervention designed to improve complementary feeding practices as a strategic approach to prevent stunting.   Method: A mixed-methods study was conducted from June to September 2024 at the Kalasan Community Health Centre, Sleman, Indonesia, involving 97 families with stunted children aged 6-24 months. The participatory intervention, structured around the Plan-Do-Check-Act (PDCA) cycle, included training, mentoring, and community support. Quantitative data were collected via validating questionnaires and analyzed using paired t-tests and Cohen’s d to calculate effect sizes. Qualitative data were gathered through focus group discussions and in-depth interviews with participants and health cadres, the analyzed thematically to understand the implementation process and contextual factors.   Result: The FCEM program led to statistically significant and substantive improvement in all domain (P<0.001). Mean scores increased by 1.40 point for knowledge, 1.65 points for health behaviors, and 1.31 points for family dynamics. Calculated effect sizes ranged from 0.82 to 1.17, indicated large intervention effect. Qualitative findings revealed enhanced family-health worker collaboration and increased confidence in preparing nutritious local foods as key facilitators.   Conclusion: The findings demonstrate that the FCEM is an effective, community-based intervention for improving complementary feeding practices and can be considered a strategic model for stunting prevention programs.   Keywords: Complementary feeding; Family empowerment; Stunting; Participatory development; Toddler